How effective is laparoscopic redo-antireflux surgery?. Issue 3 (30th December 2021) - Fuchs, K H; Breithaupt, W; Varga, G; Babic, B; Eckhoff, J; Meining, A
Summary: Background: The failure-rate after primary antireflux surgery ranges from 3 to 30%. Reasons for failures are multifactorial. The aim of this study is to gain insight into the complex reasons for, and management of, failure after antireflux surgery. Methods: Patients were selected for redo-surgery after a diagnostic workup consisting of history and physical examination, upper gastrointestinal endoscopy, quality-of-life assessment, screening for somatoform disorders, esophageal manometry, 24-hour-pH-impedance monitoring, and selective radiographic studies such as Barium-sandwich for esophageal passage and delayed gastric emptying. Perioperative and follow-up data were compiled between 2004 and 2017. Results: In total, 578 datasets were analyzed. The patient cohort undergoing a first redo-procedure ( n  = 401) consisted of 36 patients after in-house primary LF and 365 external referrals (mean age: 62.1 years [25–87]; mean BMI 26 [20–34]). The majority of patients underwent a repeated total or partial laparoscopic fundoplication. Major reasons for failure were migration and insufficient mobilization during the primary operation. With each increasing number of required redo-operations, the complexity of the redo-procedure itself increased, follow-up quality-of-life decreased (GIQLI: 106; 101; and 100), and complication rate increased (intraoperative: 6, 4–10%; postoperative: 4, 5–19%/first to third redo). After three redo-operations, resections were frequently necessary (morbidity: 42%). Conclusions: Providing a careful patient selection, primary redo-antireflux procedures have proven to be highly successful. It is often the final chance for a satisfying result may be achieved upon performing a second redo-procedure. A third revision may solve critical problems, such as severe pain and/or inadequate nutritional intake. When resection is required, quality of life cannot be entirely normalized.